Review of multi-layered magnetoelectric composite materials and devices applications. (21st May 2018) - Chu, Zhaoqiang; PourhosseiniAsl, MohammadJavad; Dong, Shuxiang
Abstract: Multiferroic materials with the coexistence of at least two ferroic orders, such as ferroelectricity, ferromagnetism, or ferroelasticity, have recently attracted ever-increasing attention due to their potential for multifunctional device applications, including magnetic and current sensors, energy harvesters, magnetoelectric (ME) random access memory and logic devices, tunable microwave devices, and ME antenna. In this article, we provide a review of the recent and ongoing research efforts in the field of multi-layered ME composites. After a brief introduction to ME composites and ME coupling mechanisms, we review recent advances in multi-layered ME composites as well as their device applications based on the direct ME effect, magnetic sensors in particular. Finally, some remaining challenges and future perspective of ME composites and their engineering applications will be discussed.